1975
DOI: 10.1152/ajplegacy.1975.228.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of blood flow in the rat kidney

Abstract: We present evidence showing that renal blood flow (RBF) in the anesthetized nondiuretic rat can be measured reliably and accurately using a noncannulating flow transducer and an electromagnetic flowmeter. In vitro calibration yielded a linear relationship (r=0.998) between flowmeter output voltage and blood flow rates from 0.2 to 10.3 ml/min. Excellent agreement was observed between simultaneous determinations of RBF by the flowmeter and the PAH clearance technique. Glomerular filtration rate and RBF for a kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 0 publications
6
44
0
Order By: Relevance
“…However, the relationship was not linear, and the threshold pressure was 96 mmHg. Meanwhile, it was demonstrated that the lowest RAP at which renal blood flow was autoregulated was approximately 100 mmHg in the anaesthetized rat (11). Thus, the threshold pressure demonstrated in the present study is very close to the lowest perfusion pressure of the renal autoregulatory range, although there are some differences between the anaesthetized and unanaesthetized condition, so that some relationship between renal autoregulatory range and threshold pressure may be considered.…”
supporting
confidence: 65%
“…However, the relationship was not linear, and the threshold pressure was 96 mmHg. Meanwhile, it was demonstrated that the lowest RAP at which renal blood flow was autoregulated was approximately 100 mmHg in the anaesthetized rat (11). Thus, the threshold pressure demonstrated in the present study is very close to the lowest perfusion pressure of the renal autoregulatory range, although there are some differences between the anaesthetized and unanaesthetized condition, so that some relationship between renal autoregulatory range and threshold pressure may be considered.…”
supporting
confidence: 65%
“…A blood flow sensor with an inner diameter of 0.6 to 0.8 mm was placed on the renal artery, allowing continuous RBF monitoring by an electromagnetic square wave flow meter (Skalar Medical, Delft, The Netherlands) [18]. Calibration of the flow probe was conducted as described previously [19].…”
Section: Methodsmentioning
confidence: 99%
“…The flow probe size was chosen that circumferentially fit closely about the arterial wall by low-power microscopic observation but did not alter urine flow rate. Calibration was conducted according to the method of Arendshorst et al (16 Responses to L-NAME and AG. In separate anesthetized NE-and sham-ARF rats, after baseline RBF measurements were determined, L-NAME (10 mg/kg) was given intravenously over 5 min.…”
Section: Methodsmentioning
confidence: 99%